PELATIHAN INOVASI DAN PEMASARAN ONLINE NUGGET PISANG UPAYA PENINGKATAN EKONOMI MASYARAKAT DESA CIHERANG KECAMATAN GUNUNG SARI KABUPATEN SERANG - Listiawati, Listiawati; Sari, Diah Permata; Sumarsih, Rani Sri (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The problem in CiCiherang Village is the abundance of bananas, but the lack of innovation and marketing still relies on conventional methods. One of the objectives of this activity is to improve the local economy by optimizing superior products. The method used is descriptive qualitative. This research resulted in the training "Online marketing training activities in the industrial era 4.0 and the manufacture of MSME products as an effort to improve the economy of the Ciherang Village community